Resilience of Male Early Childhood Education Teachers - Regina Putri; Asep Kurnia Jayadinata; Risty Justicia; Dhea Ardiyanti (Universitas PGRI Yogyakarta, 2026)
This article aims to explore the resilience and strategies employed by male early childhood education (PAUD) teachers in addressing the challenges of gender stereotypes within a female-dominated profession. This study employed a case study method using in-depth interview techniques. The data were analyzed through thematic analysis involving three male PAUD teachers. The interview results revealed that the resilience of male PAUD teachers is shaped by two main categories: internal and external factors. Internal factors include an interest in teaching, affection for children, confidence in one’s career choice, a sense of happiness, a desire to be a role model, and a personal meaning in being a PAUD teacher. External factors include support from colleagues and school administrators. In response to gender stereotypes, male teachers have developed several strategies, including fostering open communication with parents to reduce prejudice, emotionally and methodologically adapting to students, and utilizing social media to enhance their visibility and strengthen the positive image of male PAUD teachers. This study recommends the importance of more gender-inclusive institutional policies, such as anti-stereotyping training in educational institutions and the creation of fair representation in decision-making processes within PAUD settings. Keywords: resilience, male teachers, early childhood education